MANAJEMEN PEMBELAJARAN BERBASIS BLENDED LEARNING PADA MASA PANDEMI COVID-19 (STUDI KASUS DI SMAN 1 DEWANTARA ACEH UTARA) - Nuraini; Rahmati; Nazariati (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2021)
During the Covid-19 Pandemic, school educational institutions carried out online distance learning. For areas included in the green zone, face-to-face learning can be done for a limited time and adhere to health protocols. One of the learning innovations that can be carried out by madrasas / schools is Blended Learning-based learning, including at SMAN 1 Dewantara. This study aims to determine management, learning planning, and evaluation of Blended Learning-based learning at SMAN 1 Dewantara. The research used a qualitative approach with descriptive methods. Data obtained through observation, interviews, and documentation study. The results showed that at the planning stage, the school formulated a special curriculum in accordance with the Blended Learning learning model during the Covid-19 Pandemic supported by adequate learning facilities and infrastructure. At the implementation stage, there is a slight difference between theory and real data in the application of this blanded learning offline and online learning time. Dewantara SMAN 1 school implements a shift system, one day offline learning and on another day online learning, meanwhile, online learning is tailored to the needs of each teacher. At the evaluation stage, schools carry out offline and online website-based evaluations.